“Efecto de fertilizantes a base de Nitrógeno, Azufre y Magnesio en el incremento de la clorofila, proteína y rendimiento de maíz (Zea mays L.) en la zona de Babahoyo” - García Castro, Fabián Fabricio (2018)
VIII. SUMMARY The present experimental work was carried out in the "Matecito Dos" sector of the Babahoyo canton of the Province of Los Ríos, located at kilometer 21 of the Babahoyo-Pueblo Nuevo highway, with geographic coordinates UTM 79,414416 of west longitude and 1,905,498 of longitude south and an altitude of 6,7 msnm The place presents a humid tropical type climate, with an average temperature of 25.6 ° C, annual precipitation of 2329.8 mm, relative humidity of 82% and 998.2 hours of annual average heliophany. The soil is of flat topography, franc-clay texture and regular drainage. The genetic material used was the Hybrid DK - 7500 developed by the company Monsanto. The treatments were constituted by 3 doses of Urea, 2 Ammonium Sulfate and 2 doses of Magnesium Sulfate. applied 12 and 25 days after sowing. In all treatments, 40 kg / ha of P2O5 and 80 kg / ha of K2O were used as basic fertilization. The experimental design of random blocks with Factorial Arrangement (A * B * C + 1) was used with thirteen treatments and three repetitions. During the test the following agricultural practices will be carried out, such as soil preparation, sowing, irrigation, fertilization, weed control, phytosanitary control and harvesting. The evaluated data were soil analysis, foliar analysis, plant height, cob intersection height, chlorophyll content, protein content, cob diameter and length, number of leaves, humidity, number of grains per ear, yield and analysis. economic. Based on the results, it was determined that the fertilizers based on of Nitrogen, Sulfur and Magnesium increased the concentration of chlorophyll, protein and yield in the corn crop, in the Babahoyo area; the highest plant height was achieved when 348 kg / ha of Urea + 250 kg / ha of ammonium sulphate + 250 kg / ha of magnesium sulphate was applied; the diameter of the stem and the height of cob insertion of the was greater with the use of 348 kg / ha of Urea + 250 kg / ha of ammonium sulphate + 250 kg / ha of magnesium sulphate, while with these same levels the highest concentration of chlorophyll and proteins. The number of leaves per plant, the diameter and length of ear, was highest with the application of 348 kg / ha of Urea + 250 kg / ha of ammonium sulphate + 250 kg / of magnesium sulphate. The number of grains per ear, and the yield and net profit was maximized with the use of 174 kg / ha of Urea + 250 kg / ha of ammonium sulphate + 250 kg / ha of magnesium sulphate., which a net profit of $ 388.08 per ha was obtained. Although with the application of 348 kg / ha of Urea a profit of $ 442.12 per ha was obtained. Keywords: Urea, Ammonium sulfate, Magnesium sulfate, chlorophyll, protein, yield, corn.